Pembelajaran Musik Rejung Menggunakan Media Audio Visual (Video Tutorial) - Siswanto, Silo; Haque, Zely Marissa (Jurnal Seni, Desain dan Budaya)
ABSTRACTThe Learning of local music in schools and universities had become the pre-eminent material as local content in every place in Indonesia, in this case, the focus of discussion on this paper was Rejung music or often called as Batang Hari Sembilan, the identification of problems in this research was in the learning process of Rejung music, where the music educators had difficulties in teaching this material because the steps of rejung music learning material were not well compiled. In addition, the problems faced by educators in learning Rejung music was the learning media was not utilized optimally, namely, audio-visual media (learning tutorial video). Based on the identification of the problem, The problem in this research could be formulated in the form of questions as follows, 1) How was the structure of Rejung music. 2) how to make /produce tutorial video in Rejung Music learning. 3) How to learn Rejung music through tutorials video. While the specific objectives of this study were 1) Explained the music playing technique in Rejung music. 2) Explained the video tutorial production. 3) Explained the learning process of Rejung music through tutorial video. The method used in this research was this research discussed matters related to the science of Rejung music, the data collection was done through observation and documentation related to the learning process of the local music. Furthermore, the analysis of data related to Rejung music was processed and formulated through musicology and audio-visual multimedia.Keywords : Rejung Music, Tutorial Video, Learning MediaABSTRAKPembelajan musik daerah setempat di sekolah maupun perguruan tinggi menjadi materi unggulan sebagai muatan lokal disetiap tempat di Indonesia, dalam hal ini, yang menjadi fokus pembahasan tulisan ini adalah musik rejung atau sering disebut dengan Batang Hari Sembilan, identifikasi masalah dalam penelitian ini yakni proses pembelajaran musik rejung, kesulitan bagi pendidik musik dalam mengajarkannya yakni, belum tersusunnya langkah-langkah materi pembelajaran musik ?rejung dengan baik. Selain itu, masalah yang dihadapi pendidik dalam pembelajaran musik rejung, tidak termanfaatkan media pembelajaran secara optimal yaitu, media audio visual (video tutorial pembelajaran). Berdasarkan identifikasi masalah tersebut, dapat dirumuskan masalah dalam penelitian ini berupa pertanyaan sebagai berikut, 1) Bagaimana struktur musik rejung. 2) bagaimana cara pembuatan/produksi video tutorial dalam pembelajaran Musik Rejung. 3) Bagaimana belajar musik Rejung melaui Video tutorial. Sedangkan tujuan khusus dari penelitian ini adalah 1) Menjelaskan teknik permianan pada musik Rejung. 2) Menjelaskan produksi video tutorial. 3) Menjelaskan proses pembelajaran musik rejung melalui video tutorial. Metode yang digunakan pada penelitian yakni Penelitian ini membahas hal-hal yang terkait dengan keilmuan musik rejung, dalam pengumpulan datanya dilakukan melalui observasi dan dokumentasi yang terkait dengan proses pembelajaran musik daerah setempat. Selanjutnya analisis data-data yang berhubungan dengan musik rejung tersebut diolah dan dirumuskan melalui musikologi dan multimedia audio visual.Kata Kunci : Musik Rejung, Video Tutorial, ?Media Pembelajaran